2013
DOI: 10.1371/journal.pone.0069647
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Pleurodeles waltl DNA Polymerase mu Expression by Extreme Conditions Encountered during Spaceflight

Abstract: DNA polymerase µ is involved in DNA repair, V(D)J recombination and likely somatic hypermutation of immunoglobulin genes. Our previous studies demonstrated that spaceflight conditions affect immunoglobulin gene expression and somatic hypermutation frequency. Consequently, we questioned whether Polμ expression could also be affected. To address this question, we characterized Polμ of the Iberian ribbed newt Pleurodeles waltl and exposed embryos of that species to spaceflight conditions or to environmental modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…An assessment of the impact of hypergravity on the similarly assembled T cell receptor repertoire of neonatal mice showed low correlation of individual Beta chain V- and J-gene segment recombination frequencies between control animals and animals subjected to centrifugation. 85% of gene V/J-gene segment combinations were not shared among the two treatment groups (Ghislin et al, 2015) and the differences could be attributed to changes in somatic recombination machinery under altered gravity conditions (Schenten et al, 2013, Ghislin et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…An assessment of the impact of hypergravity on the similarly assembled T cell receptor repertoire of neonatal mice showed low correlation of individual Beta chain V- and J-gene segment recombination frequencies between control animals and animals subjected to centrifugation. 85% of gene V/J-gene segment combinations were not shared among the two treatment groups (Ghislin et al, 2015) and the differences could be attributed to changes in somatic recombination machinery under altered gravity conditions (Schenten et al, 2013, Ghislin et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…61 Amphibians are interesting models for analyzing the effects of spaceflight on the immune system because cardinal elements of the adaptive immune system are shared by all gnathostomes. 1 , 62–69 Later on, adult P. waltl were immunized with protein onboard the Mir space station. The analysis of these animals revealed an increase of IgY heavy chain mRNAs (IgY is the physiological counterpart of human IgA 66 ) in the spleen of flown animals.…”
Section: Introductionmentioning
confidence: 99%
“…Also, transcriptome analysis was carried out on the ground using low-dose irradiation and modeled microgravity showing multiple altered neurological pathways [ 61 ] or a hematological system with transforming growth factor β signaling [ 62 ]. During the flight on the ISS for 10 days, a decrease in the expression of the newt ( Pleurodeles waltl ) gene of DNA repair (Pol mu) was observed due to the space radiation or microgravity [ 63 ]. Comprehensive analyses of transcripts have been carried out on the International Space Station to examine the effects of space radiation and microgravity on animals, and it was found that the expression of several microRNAs in blood might regulate the TGFβ1 gene, which is a master regulator coordinating for a systemic response to microgravity and space radiation [ 64 ].…”
Section: Discussionmentioning
confidence: 99%